Islet Dysfunction in a Novel Transgenic Model of T Cell Insulitis - Emily Esakov; Neha Nandedkar-Kulkarni; Ali G. Al-Dieri; Hannah Hafner; Brigid Gregg; Marcia F. McInerney (Biomolecules, 2021)
The newly established CD3FLAG-mIR transgenic mouse model on a C57Bl/6 background has a FLAG tag on the mouse Insulin Receptor (mIR), specifically on T cells, as the FLAG-tagged mIR gene was engineered behind CD3 promoter and enhancer. The IR is a chemotactic molecule for insulin and the Flag-tagged mIR T cells in the BL/6-CD3FLAGmIR transgenic mice can migrate into the pancreas, as shown by immunofluorescent staining. While the transgenic mice do not become diabetic, there are phenotypic and metabolic changes in the islets. The transgenic islets become enlarged and disorganized by 15 weeks and those phenotypes continue out to 35 weeks of age. We examined the islets by RT-PCR for cell markers, ER stress markers, beta cell proliferation markers, and cytokines, as well as measuring serum insulin and insulin content in the pancreas at 15, 25, and 35 weeks of age. In transgenic mice, insulin in serum was increased at 15 weeks of age and glucose intolerance developed by 25 weeks of age. Passage of transgenic spleen cells into C57Bl/6 RAG−/− mice resulted in enlarged and disorganized islets with T infiltration by 4 to 5 weeks post-transfer, replicating the transgenic mouse studies. Therefore, migration of non-antigen-specific T cells into islets has ramifications for islet organization and function.